Prosthetic Approach Following Traumatic Evisceration: A Case Report - Juanita, Mariska; Ramdhani, Riezky; Dammar, Irfan (Indonesian Journal of Prosthodontic, 2021)
Patient Chief Complaint: A 20-year-old male patient was referred to Prosthodontic Department Hasanuddin University Dental Hospital, Makassar with disfiguration of the face as chief complaint. Medical history revealed a significant trauma to the left eye 6 months ago which had been thereafter eviscerated. Patient has never used prosthetic eye afterwards. Patient Status: Examination of the left eye socket revealed a healthy conjunctiva covering the posterior wall of the anophthalmic socket with synchronous motions and absence of infection or inflammation signs. Sulcus depth was sufficient to retain prosthetic eye. Treatment Plan: Rehabilitation of the ocular defect with customized acrylic-based ocular prosthesis to increase patient’s appearance and to prevent further shrinkage of the eye socket. Details of Therapy: Preliminary impression was done using customized tray fabricated from modelling wax and hydrocolloid irreversible impression material. An intraocular custom tray for secondary impression was fabricated with acrylic resin and modified with a syringe that attached to the custom tray. Secondary impression of the defect was recorded using polyvinyl siloxane light viscosity material followed by wax pattern fabrication using modelling wax. The wax pattern was tried in patient’s socket and checked for size, comfort, support, fullness, and then packed with tooth colored heat cure acrylic resin. After determining the location and diameter of the iris with an optical vernier pupillary distance ruler, the color of sclera was determined by shade guide and confirmed with technician using digital photo. Ocular prosthesis was fabricated afterwards and inserted into the eye socket and evaluated for suitability, aesthetic, and movements with the contralateral eye. Clinical Significance: Customized ocular prosthesis was significantly more aesthetic than pre-fabricated one with better contouring, color matching, and coordinated movements with the contralateral eye. This prosthetic approach may restore patient’s appearance, thus increase their self-esteem, and improve the quality of life.